ANALISIS PENGARUH MODAL DAN TENAGA KERJA TERHADAP PRODUKSI GENTENG DI DESA UREK-UREK KECAMATAN GONDANGLEGI KABUPATEN MALANG - Theo Dwiki Erlangga; Muhammad Faisal Abdullah; Sudarti (Jurnal Ilmu Ekonomi JIE, 2019)
Abstract :This study aims to determine and analyze the influence of factors of production capital and labor to the production of tile and efficiency of the production of tiles in the village Urek-urek Gondanglegi District of Malang. This study uses variables consisting of capital and labor. The the sampling technique used is Simple Random Sampling. Data collected with secondary data and primary. The analysis use are the assumptions of classical, the analysis of the regression of the liniear risk using the production Coob-Douglas, the statistics analysis and effeciency of the production of tiles. The test results of a partial to show that labor have a significant effect on the tiles. The capital didn’t have a significant effect on the tiles. Then the results of the efficiency of business production obtained figures of 2,312 the meaning of the business plate is an efficient.Keywords:Captial, Labor, Production Results, Business efficiency.